2017
DOI: 10.1371/journal.pntd.0005697
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of invasive Salmonella Typhimurium ST313 in animal models of infection

Abstract: Salmonella Typhimurium sequence type (ST) 313 produces septicemia in infants in sub-Saharan Africa. Although there are known genetic and phenotypic differences between ST313 strains and gastroenteritis-associated ST19 strains, conflicting data about the in vivo virulence of ST313 strains have been reported. To resolve these differences, we tested clinical Salmonella Typhimurium ST313 and ST19 strains in murine and rhesus macaque infection models. The 50% lethal dose (LD50) was determined for three Salmonella T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Lineage II appears to have largely replaced Lineage I since 2004, and it has been suggested this is due to Lineage II possessing a gene encoding chloramphenicol resistance [ 47 ]. Laboratory characterization of Lineage II strains has shown that they are not host-restricted [ 52 , 53 ], but do appear to possess characteristics suggestive of adaptation to an invasive lifestyle [ 54 57 ], though it is important to note that this is a complex trait and not easily quantified.…”
Section: Resultsmentioning
confidence: 99%
“…Lineage II appears to have largely replaced Lineage I since 2004, and it has been suggested this is due to Lineage II possessing a gene encoding chloramphenicol resistance [ 47 ]. Laboratory characterization of Lineage II strains has shown that they are not host-restricted [ 52 , 53 ], but do appear to possess characteristics suggestive of adaptation to an invasive lifestyle [ 54 57 ], though it is important to note that this is a complex trait and not easily quantified.…”
Section: Resultsmentioning
confidence: 99%
“…Mice are not typically suitable as an adapted model for S. Typhimurium, as these bacteria induce a typhoid-like systemic illness that leads to death of the animals. Although the 50% lethal dose (LD 50 ) was not reported to be significantly different between ST313- and ST19-infected mice ( 87 , 93 ). Further, there was no consistent difference in the inflammatory response ( 79 , 88 , 93 , 126 ) or in the ability of the bacteria to colonize the intestinal tract and to disseminate in the body ( 79 , 87 , 88 , 92 , 93 , 126 ).…”
Section: Host–pathogen Interaction Of Intsmentioning
confidence: 96%
“…In addition, several ST313 strains express less flagellin, a component of the flagellum appendage responsible for bacterial motility ( 91 , 92 ). Indeed, ST313 strains (D65, Q55, S11, S12, D23580, and A130) were reported to be less motile than ST19 strains (I77, I89, I41, S52, and SL1344) ( 91 , 93 ), although some variability among the strains was observed ( 87 ). These data suggest that, like Salmonella Typhi, Salmonella Typhimurium ST313 lack some of the mechanisms that allow transmission and/or survival in the environment.…”
Section: Unique Intrinsic Properties Of Invasive Non-typhoidal Salmonmentioning
confidence: 99%
“…Experimental infections of mice and primates largely support the view that ST313 strains have altered pathogenicity compared with those of commonly used laboratory strains, such as strains SL1344 and ATCC 14028. An ST313 isolate hyperdisseminated from the intestine to systemic sites in the murine model of infection and in poultry ( 16 , 17 , 53 ). Furthermore, ST313 strains exhibit decreases in intestinal pathology in mice, fluid accumulation and migration of inflammatory cells to the intestinal lumen in bovine ileal loops, and diarrhea in rhesus macaques ( 53 , 54 ).…”
Section: Epidemiology and Host Range Of Salmonella mentioning
confidence: 99%